Literature Review: Application of Video Learning Media in Learning Figures in Elementary Schools - Chandra Puspita; Alya Cahyani; Amalia Putri Annisa; Fatkhul Arifin (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
The problem in learning flat shapes in elementary schools is that students' understanding of abstract geometric concepts is still lacking and students' learning motivation is weak. This research aims to analyze literature that examines the role of video media in increasing students' understanding and learning motivation, especially regarding the concept of plane shapes. The method used is a bibliographic review, collection and analysis of research published in the last 10 years. Selected studies were analyzed based on study aims, methods, population, results, and implications. The results of the literature review show that video learning media can increase students' understanding of the concept of plane figures and increase learning motivation. Learning videos provide clear and interactive visuals that help students better understand abstract concepts. The conclusion of this research is that video media has great potential to improve learning about forms of planning in elementary schools, but its implementation requires careful planning and adequate technical support. Apart from that, it is also important to train teachers to use video media to increase their effectiveness.